Public enemies - Burrough, Bryan; Goldenthal, Elliot 1954-; Burrough, Bryan (Universal Pictures, 2009)
No one could stop Dillinger and his gang. No jail could hold him. His charm and audacious jailbreaks endeared him to almost everyone, from his girlfriend Billie Frechette to an American public who had no sympathy for the banks that had plunged the country into the Depression. But while the adventures of Dillinger's gang thrilled many, Hoover made Dillinger America's first Public Enemy Number One.
Bildformat 2.40:1 (anamorph widescreen)
Orig.: USA 2009
Enth. Legendär : Feinde ; Michael Mann: Die Entstehung von "Public enemies" ; Der letzte der legendären Verbrecher ; Auf den Spuren Dillingers: die echten Drehorte ; Die Technologie der Verbrecher ; Filmkommentare vpm Regisseur Michael Mann
Keywords: Dillinger, John <1903-1934> -- Drama; Floyd, Pretty Boy <1904-1934> -- Drama; Purvis, Melvin <1903-1960> -- Drama; United States. -- Federal Bureau of Investigation -- Drama; Investigación criminal - Illinois - Chicago - Teatro; Robos bancarios - Estados Unidos - Teatro; Bank robberies -- United States -- Drama; Criminal behavior -- United States -- Drama; Criminal investigation -- Illinois -- Chicago -- Drama; USA; Biographical films; Crime films; Feature films; Thrillers (Motion pictures); Video recordings for the hearing impaired